Influência da defesa indireta e direta de plantas de milho induzidas por voláteis sintéticos sobre o Dichelops melacanthus (Hemiptera: Pentatomidae) - Nascimento, Izabela Nunes do (2020)
Maize, Zea mays L., is the most produced cereal in the world. One of the main factors that compromises the yield and the quality of production is the incidence of pests, being Dichelops melacanthus, the most important bug species that attacks this crop in South America. The response of plants to the attack of herbivores can lead to a increase in the production of volatile and non-volatile secondary metabolites, which act in the direct and indirect defenses of plants. The objective of this study was to characterize the chemical profile of corn plants, healthy and after the herbivory of the bug D. melacanthus, exposed or not to synthetic volatiles induced by herbivory (VIPHs); to evaluate the behavioral response of the parasitoid Telenomus podisi and the herbivore D. melacanthus to the volatiles released by corn plants submitted to different treatments and to investigate whether corn plants attacked by the bug D. melacanthus, exposed to synthetic patterns of VIPHs have altered concentrations of benzoxazinoids , as well as to verify if D. melacanthus is affected by different levels of these compounds in maize. The research was developed in three experiments. In the first, healthy plants were submitted or not to the herbivory of the bug D. melacanthus. The volatiles of the plants were collected by the aeration technique. To evaluate whether the D. melacanthus herbivory affects or not the search behavior of the natural enemy T. podisi and of co-specific females, bioassays were performed in a “Y” olfactometer. In the second experiment, the production of volatile compounds from corn plants exposed to VIPHs was evaluated. The plants were exposed to the compounds (RS) -linalol and (E)--farnesene and used in olfactometry bioassays, to assess whether the volatiles emitted by plants exposed to VIPHs and whether or not treated with D. melacanthus herbivory affect behavior search for T. podisi and co-specific females. In the third experiment, the production of benzoxazinoids from corn plants exposed to synthetic VIPHs was evaluated. Then, they received or not females of D. melacanthus and were subjected to a liquid-liquid extraction. To assess whether plants subjected to volatiles had their direct defense activated, plants exposed or not to VIPHs, they were offered as food for adults of D. melacanthus and the parameters of fertility, fertility and longevity were evaluated. The chemical analysis of volatiles collected during aeration showed that the injury of D. melacanthus induced the plant to produce a different profile of volatile organic compounds, compared to healthy plants. The parasitoid T. podisi responded preferentially to the odors released by plants submitted to herbivory when compared to the odors of healthy plants for 24-48 h after the start of treatment. The synthetic volatile compounds (RS) -linalol and (E)-karyophylene induced an increase in the production of volatiles after the plants suffered damage from D. melacanthus. The results obtained indicate that the exogenous treatment of the corn plants with the selected compounds changed their chemical profile, but does not improve the indirect defense of the plants against the herbivore D. Melacanthus.